Kesiapan untuk Berubah dengan Tingkat Stres Kerja Pegawai Direktorat Jendral Pajak - Rismaya Banjar Amanda (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2008)
The present study examined the correlation between the ability-to-change and level of stress among 71 staffs of DJP (Direktorat Jendral Pajak) with at least has been working for a year as staff at the same organization. Data was collected using The Ability to Change's Scale (Zaccaro In Callarco & Gurvis, 2006) and The Work Stress Scale (Robbins, 1986). We found that the high level ability-to-change within the staffs, has significant effect on the moderate level of work stress they encounter (r = -0,246; p = 0,019). Moreover, using simple regression technique, the result found out that the emotional fexibility has the most significant effect in reducing work stress among 2 other aspects of the ability to change (cognitive and disposition flexibility).